Fibrinogen levels compensation of thrombocytopenia-induced bleeding following cardiac surgery. (15th December 2017) - Ranucci, Marco; Baryshnikova, Ekaterina; Ranucci, Matteo; Silvetti, Simona; ,
Abstract: Background: After cardiopulmonary bypass (CPB) thrombocytopenia is a relatively common pattern which may trigger postoperative bleeding. The purpose of this study is to verify if the endogenous fibrinogen levels are independent determinants of chest drain blood loss and need for allogeneic blood products transfusions in a clinical model of post-CPB thrombocytopenia. Methods: Retrospective analysis on 445 consecutive patients having a platelet count < 100 × 1000 cells/μL after CPB. Based on the fibrinogen levels the patients were divided into three groups with similar platelet count and low (LF, median 170 mg/dL), intermediate (IF, median 215 mg/dL), and high (HF, median 280 mg/dL), fibrinogen levels. Chest drain blood loss (mL/12 h), transfusion rate of red blood cells (RBC), fresh frozen plasma (FFP) and platelet concentrates were assessed and compared between groups. Results: There was a significant (P = 0.001) difference in chest drain blood loss with higher values in the LF group (487 mL/12 h, IQR 300–600 mL/12 h) than in the IF group (350 mL/12 h, IQR 200–500 mL/12 h) and the HF group (300 mL/12 h, IQR 200–475 mL/12 h). Transfusion rates of FFP significantly (P = 0.014) differed between groups (LF: 18.4%, IF: 7.9%, HF: 9.2%) and platelet concentrate transfusions significantly (P = 0.020) differed between groups (LF: 23.5%, IF: 16.5%, HF: 10.7%). In multivariable models, these differences were confirmed. Thromboelastography parameters showed an effective compensation of clot firmness in group HF vs. IF and LF. Conclusions: Levels of fibrinogen > 240 mg/dL compensate the decrease in clot firmness observed in thrombocytopenic patients following CPB, and reduce bleeding and transfusion needs.